"Diseño organizacional de la empresa Reybanpac e la zona de Quevedo". - Ponce Vásquez, Ronald Paul (2012)
The present investigation you carries out in the headquarters central area of Quevedo (the areas of Shrimps, Valencia and San Camilo Understand) with the following objectives. A. To Propose an organizational structure for the company Reybanpac in the area of Quevedo. B. To determine the complexity of the organizational structure of the Company and to identify the formalization that governs it in the area of Quevedo. C. To Establish the design of the new organization based on the basic dimensions of their organizational structure. It is summarized that the used methodology, to carry out the present investigation, theoretically they concern to the study of the structure of a system that can be appreciated with the analysis of three basic dimensions the size, the complexity and the formalization .................................................................................